(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Anthropogenic activity produces domestic and agricultural wastes that are distributed to the waters which can affect the high and low levels of total organic carbon and phosphate from these waters. The purpose of this research was to analyze the total organic carbon content and phosphate and analyze the distribution and the correlation of total organic carbon and phosphate in sediments of the Banyuasin Estuary, South Sumatra. This research was conducted in November 2019. Sampling of sediments using purposive method at 10 stations during low tide. Analysis of total organic carbon using Ash Content method according to SNI 01-2891-1992, and phosphate analysis using the Bray and Kurtz method. Distribution patterns of total organic carbon concentration and phosphate were analyzed using Surfer 9. Correlation analysis was conducted with Ms. Excel. The results showed that the total organic carbon concentration ranged from 3.71 - 7.42% and the phosphate concentration ranged from 16.49 mg/kg - 26.45 mg/kg. The distribution of total organic carbon and phosphate is influenced by the type of sediment substrate at each station. Smoother sediments have higher total organic matter and phosphate content. Total organic carbon and phosphate in the Banyuasin Estuary waters have a positive and strong correlation which indicates that the higher the total organic carbon content in the waters, the higher the phosphate content.